Glutamate regulates the viability of retinal cells in culture - Rego, A. Cristina (2001)
In this study, we show that glutamate regulates the viability of cultured retinal cells upon transient glucose deprivation. At low concentrations (10-100 [mu]M) glutamate decreased MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] reduction to about 50% of control and decreased intracellular ATP levels (about 4-fold) after transient glucose removal. Under these conditions, the decrease in MTT reduction was associated with the activation of NMDA (N-methyl--aspartate) receptors. Upon exposure to high (10 mM) glutamate and transient glucose deprivation, the intracellular levels of glutamate increased. High glutamate significantly counteracted the decrease in MTT reduction and ATP production observed in the presence of low glutamate concentrations. AOAA (aminooxyacetic acid), a non-specific inhibitor of mitochondrial transaminases, enhanced the intracellular glutamate levels, but did not largely affect glutamate-mediated changes in MTT reduction or ATP production. Furthermore, the intracellular levels of pyruvate were not significantly altered, suggesting that changes in ATP production were not due to an increase in glycolysis. Thus, the recovery from glucose deprivation seems to be facilitated in retinal neuronal cells that had been exposed to high glutamate, in comparison with low glutamate, suggesting a role for high glutamate and glucose in maintaining retinal cell function following conditions of glucose scarcity.